2018
DOI: 10.1101/sqb.2018.83.038158
|View full text |Cite
|
Sign up to set email alerts
|

Rewiring the Addicted Brain: Circuits-Based Treatment for Addiction

Abstract: The advent of the noninvasive brain stimulation (NIBS) technique has paved the way for neural circuit-based treatments for addiction. Recently, evidence from both preclinical and clinical studies has evaluated the use of transcranial magnetic stimulation (TMS) as a safe and cost-effective therapeutic tool for substance use disorders (SUDs). Indeed, repetitive TMS impacts on neural activity inducing short-and long-term effects involving neuroplasticity mechanisms locally within the target area of stimulation an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 93 publications
0
8
0
Order By: Relevance
“…His initial mouse study showed that prolonged cocaine self-administration decreases the intrinsic excitability of pyramidal neurons in the prelimbic cortex (Chen et al 2013). Through a series of fortuitous events, this research led to pilot studies in cocaine-addicted patients, revealing that transcranial magnetic stimulation (TMS) of dorsolateral prefrontal cortex reduces cocaine cravings and use (Madeo and Bonci 2019). Lui-hai Tsai presented a remarkable discovery that 40-Hz visual flicker reduces amyloid β in mouse models of Alzheimer's (Iaccarino et al 2016).…”
Section: Curiosity-driven Science Connects With the Clinicmentioning
confidence: 99%
See 1 more Smart Citation
“…His initial mouse study showed that prolonged cocaine self-administration decreases the intrinsic excitability of pyramidal neurons in the prelimbic cortex (Chen et al 2013). Through a series of fortuitous events, this research led to pilot studies in cocaine-addicted patients, revealing that transcranial magnetic stimulation (TMS) of dorsolateral prefrontal cortex reduces cocaine cravings and use (Madeo and Bonci 2019). Lui-hai Tsai presented a remarkable discovery that 40-Hz visual flicker reduces amyloid β in mouse models of Alzheimer's (Iaccarino et al 2016).…”
Section: Curiosity-driven Science Connects With the Clinicmentioning
confidence: 99%
“…A less-invasive but also less-specific technique, transcranial magnetic stimulation, has also been gaining ground in treating major depression and anorexia. Antonello Bonci discussed how his group moved from a mouse model of compulsive drug use to TMS stimulation of dorsolateral cortex for ameliorating cocaine craving and drug use (Chen et al 2013;Madeo and Bonci 2019) and discussed several ongoing clinical trials building on their pilot studies. A continuing challenge for both DBS and TMS is the limited mechanistic understanding of their effects, a situation that is quickly changing.…”
Section: -David Andersonmentioning
confidence: 99%
“…Our current knowledge of the circuits involved in addiction comes from animal studies as the pathways and brain regions involved are similar in rodents and humans (Kalivas et al, 2006;Madeo and Bonci, 2019). Animal models of addiction are one of the most well-developed and validated models in neuropsychiatric research and are used by researchers and clinicians to gain insight into some of the mechanisms involved in addiction (Kalivas et al, 2006;Venniro et al, 2016).…”
Section: Manipulating Circuits Involved In Addictionmentioning
confidence: 99%
“…In addition, because compulsive drug use has been associated with abnormal orbitofrontal-and mesolimbic-striatal circuits in subjects who are punishment resistant (i.e. even when faced with consequences, subjects continue to pursue the drug) (Hu et al, 2019), the possibility of using rTMS to stimulate hypoactive prefrontal cortical neurons, which can then modulate interconnected networks, is appealing (Diana et al, 2017;Madeo and Bonci, 2019;Song et al, 2019). An increasing number of studies have shown anticraving effects following rTMS treatment targeting the PFC (see Ma et al, 2019;Madeo and Bonci, 2019;Zhang et al, 2019), presumably through modulation of the efferent glutamatergic and afferent dopaminergic connections (Diana, 2011;Diana et al, 2017; Figure 1).…”
Section: Rtms In Cocaine and Methamphetamine Abuse -Clinical Researchmentioning
confidence: 99%
See 1 more Smart Citation